Atmospheric chemistry and physics from air pollution to climate change - Seinfeld, John H.; Pandis, Spyros N. 1963-. (Hoboken, New Jersey John Wiley & Sons, Inc., 2016)
A detailed account of the chemistry and physics of the atmosphere - for graduate students, professionals and libraries involved in environmental, civil and chemical engineering projects and studies.
Dr. Jonnifer R. Sinogaya (Recommending faculty) - Bookfair2017
Includes bibliographical references and index.
Keywords: Atmospheric chemistry; Air -- Pollution; Environmental chemistry